Baicalein Alleviates Arsenic-induced Oxidative Stress through Activation of the Keap1/Nrf2 Signalling Pathway in Normal Human Liver Cells - Wang, Qi; Zhang, Aihua (Current Molecular Medicine, 2024)
Background: Oxidative stress is a key mechanism underlying arsenicinduced liver injury, the Kelch-like epichlorohydrin-related protein 1 (Keap1)/nuclear factor E2 related factor 2 (Nrf2) pathway is the main regulatory pathway involved in antioxidant protein and phase II detoxification enzyme expression. The aim of the present study was to investigate the role and mechanism of baicalein in the alleviation of arsenic-induced oxidative stress in normal human liver cells. Methods: Normal human liver cells (MIHA cells) were treated with NaAsO2 (0, 5, 10, 20 μM) to observe the effect of different doses of NaAsO2 on MIHA cells. In addition, the cells were treated with DMSO (0.1%), NaAsO2 (20 μM), or a combination of NaAsO2 (20 μM) and Baicalein (25, 50 or 100 μM) for 24 h to observe the antagonistic effect of Baicalein on NaAsO2. Cell viability was determined using a Cell Counting Kit- 8 (CCK-8 kit). The intervention doses of baicalein in subsequent experiments were determined to be 25, 50 and 100μM. The intracellular content of reactive oxygen species (ROS) was assessed using a 2′,7′-dichlorodihydrofluorescein diacetate (DCFHDA) probe kit. The malonaldehyde (MDA), Cu-Zn superoxide dismutase (Cu-Zn SOD) and glutathione peroxidase (GSH-Px) activities were determined by a test kit. The expression levels of key genes and proteins were determined by real-time fluorescence quantitative polymerase chain reaction (qPCR) and Western blotting. Results: Baicalein upregulated the protein expression levels of phosphorylated Nrf2 (p-Nrf2) and nuclear Nrf2, inhibited the downregulation of Nrf2 target genes induced by arsenic, and decreased the production of ROS and MDA. These results demonstrate that baicalein promotes Nrf2 nuclear translocation by upregulating p-Nrf2 and inhibiting the downregulation of Nrf2 target genes in arsenic-treated MIHA cells, thereby enhancing the antioxidant capacity of cells and reducing oxidative stress. Conclusion: Baicalein alleviated arsenic-induced oxidative stress through activation of the Keap1/Nrf2 signalling pathway in normal human liver cells.
Keywords: oxidative stress